PENGARUH MEDIA BUSY BOOK TERHADAP KESADARAN TUBUH (BODY AWARENESS) ANAK USIA 5-6 TAHUN DI TK SHAFA MARWAH - Amelia; Rina Syafrida; Nancy Riana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the impact of using Busy Book media on body awareness in children aged 5 to 6 years at Shafa Marwah Kindergarten. This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research sample consisted of 15 children selected through simple random sampling. Data collection was carried out through observation using an assessment sheet that had undergone validity and reliability testing, while data analysis included descriptive statistics, normality and hypothesis testing using the Paired Sample t-Test. The results showed that before the treatment, children's body awareness was in the "Beginning to Develop" (MB) category, with a mean score of 42.60. After the treatment using Busy Book media, the mean score increased to 57.93, placing it in the "Developing as Expected" (BSH) category. The hypothesis test yielded t = 11.010 (df = 14) with a significance value (Sig. 2-tailed) of p < 0.001, meaning H0 was rejected and Ha was accepted. This confirms that Busy Book media has a significant effect on improving children's body awareness. Busy Book media proved effective in helping children recognize their body parts and functions, understand body identity, recognize physical body boundaries, respond to potentially harmful situations, and understand body privacy limits. This media can serve as an educational resource for teachers to stimulate early childhood body awareness from an early age.